Association Between Walking Speed and Urinary Incontinence in the Older Women. Which Patients Should be Referred to Geriatricians? - Atmis, Volkan; Guler, Basak (Gynecology Obstetrics & Reproductive Medicine, 2020)
OBJECTIVE: Primary end-point of this study was to detect if there is an association between walking speed and urinary incontinence in older women and secondarily to detect an association between urinary incontinence with other geriatric syndromes. STUDY DESIGN: This is a prospective and cross-sectional study. Three hundred and eighty-nine old aged women admitted to the Geriatrics Department of Ankara University were enrolled and urinary incontinence and type of urinary incontinence, Handgrip strength test, Timed up and Go test, Katz Index of Independence in Activities of Daily Living, Lawton Index of Instrumental Activities of Daily Living, Mini Nutritional Assessment, Mini-Mental State Evaluation, Geriatric Depression Scale, Body Mass Index (BMI) of these participants were recorded. Association of urinary incontinence and these parameters were analyzed. RESULTS: The median age of the study population was 68 (58-86 years of age). Two hundred and fifty-eight (66.32%) had hypertension, 122 (31.36%) had diabetes mellitus, 51 (13.11%) had asthma/Chronic obstructive lung disease, 49 (12.59%) had coronary artery disease and 9 (2.31%) had cerebrovascular disease. One hundred and seventy-eight (45.7%) patients had urinary incontinence (88 urge, 55 stress, 35 mixed). One hundred and eight (27.76%) of patients had Mini-Mental State Evaluation score ≤23. Patients with urinary incontinence detected to have a longer duration of Timed Up and Go test, higher Geriatric Depression Scale score and BMI with p-values 0.005, 0.004, and <0.01 respectively; and lower Activities of Daily Living (Katz-Activities of Daily Living) score with a p-value of <0.01 results. Mini-Mental State Evaluation and Mini Nutritional Assessment scores were not statistically different between the continent and incontinent group. CONCLUSION: Whenever urinary incontinence is detected in an older woman, geriatrician referral should be considered since urinary incontinence is associated with decreased walking speed, Handgrip strength test, Activities of Daily Living, Instrumental Activities of Daily Living or increased Geriatric Depression Scale; any of which is a symptom or result of at least one geriatric syndrome.